Rozstrzygnięcie teorii gier w modelowaniu ubezpieczenia od skutków bezrobocia - Przybylska-Mazur, Agnieszka (Settlement of Game Theory in the Modelling of Unemployment Effects Insurance, 2008)
Unemployment is one of types of social risk. The insurance of unemployment has the important effect for economy and for the public assistance of society. Therefore the unemployment insurance is well-known in many countries. In last years insurance products which compensate for financial effects of job loss have been introduced also in the Polish market. In this paper the author presents the model of unemployment insurance. Using techniques and the concepts of game theory she investigates the objectives and the optimal strategy of an unemployed that seeks the job as well as the objectives and the optimal strategy of an insurer.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 27, s. 77-85